NILAI GIZI SELAI UBI JALAR DAN BELIMBING WULUH - Dwi Yanti A Astuti; Jumirah .; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The sweet potato was the local food that rich nutrient of content and its amount has increased from year to the year but the sweet potato in Indonesia has not been considered as the important commodity to consumed in a suistainable way.  Blimbi was onest the fruit that spread a lot in  Indonesia  which the process is very seldom to be consumed because that fruit has an high acid  power taste and the short ability of saving relatively.  Jam was the favourite food for everyone from child until adult. Jams are generally made with additional ingredients such as sugar, butter, citric acid and fruits that is often made into jams generally like pineapples, strawberries, blue berries etc. This research aimed to know nutrient content with include Ca, P, and KH of jam that make from a mixture of sweet potatoes and bilimbi with comparison 50%:50% and 60%:40% with three different types of sweet potatoes. This research was a randomized experimental design were divided into three groups with two treatments there are A1(50%:50%), A2(60%:40%), B1(50%:50%), B2(60%:40%), C1(50%:50%), C2(60%:40%). The analysis of nutrient has done in The Industrial Laboratorium Research and Standarization Agency Medan. The analysis of nutrient content has done with methods of AAS for calcium, spectrophotometry for phosphorus, and luff schoorl for carbohydrates. The data were analyzed in a descriptive. The results showed the characteristics of jams in the third group to the aroma like jams and typical sweet potato, it tastes a bit sour and sweet, creamy and slightly rough texture, and color was different for the three types of sweet potatoes (white, orange, purple).The nutrient of content per 100 gram of carbohydrates A1(26,6 gr), A2(25,6gr), B1(27,8gr), B2(26,6gr), C1(27,4 gr), C2(27,9 gr), and phosphorus A1(15,44 mg), A2(18,03 mg), B1(21,81 mg), B2(29,06 mg), C1(9,63 mg), C2(8,80 mg), and calcium A1(15,40 mg), A2(16,47 mg), B1(20,25 mg), B2(24,06 mg), C1(5,9 mg), C2(7,87 mg). It was suggested to the consumer to more consume of the jam  sweet potato of orange than the other two types of sweet potatoes, and than as one of the alternative result of processing food having more nutrient content. Keywords        : sweet potato, bilimbi, jam, nutrient content.